A 17q12 allele is associated with altered NK cell subsets and function - Xia, Zongqi; Liu, Qingquan; Berger, Christoph T; Keenan, Brendan T; Kaliszewska, Anna; Cheney, Patrick C; Srivastava, Gyan P; Castillo, Irene Wood; De Jager, Philip L; Alter, Galit (The Journal of immunology (1950), 2012)
NK cells play an important role in innate immunity. A previous genome-wide association study demonstrated an association between a 17q12 allele (rs9916629(C)) and lower frequency of CD3(-)CD56(+) NK cells in peripheral blood. We performed an analysis that not only replicates the original result of the genome-wide association study (p = 0.036) but also defines the specific cell subpopulations and functions that are modulated by the rs9916629 polymorphism in a cohort of 96 healthy adult subjects using targeted multiparameter flow cytometric profiling of NK cell phenotypes and functions. We found that rs9916629(C) is associated with alterations in specific NK cell subsets, including lower frequency of predominantly cytotoxic CD56(dim) NK cells (p = 0.011), higher frequency of predominantly regulatory CD56(bright) NK cells (p = 0.019), and a higher proportion of NK cells expressing the inhibitory NKG2A receptor (p = 0.0002). Functionally, rs9916629(C) is associated with decreased secretion of macrophage inflammatory protein-1β by NK cells in the context of Ab-dependent cell-mediated cytotoxicity (p = 0.039) and increased degranulation in response to MHC class I-deficient B cells (p = 0.017). Transcriptional profiling of NK cells suggests that rs9916629 influences the expression of transcription factors such as TBX21, which has a role in NK cell differentiation, offering a possible mechanism for the phenotypic and functional differences between the different alleles. The rs9916629(C) allele therefore has a validated effect on the proportion of NK cells in peripheral blood and skews NK cells toward a specific phenotypic and functional profile, potentially influencing the impact that these innate immune cells have on infection and autoimmunity.